Psychometric Properties of the Cyprus Lexical List in the Greek Language for Infants and Preschool Children and Preliminary Results - Helidoni, Meropi; Okalidou, Areti; Economou, Alexandra; Spyropoulou, Elli; Petinou, Kakia (My University, 2022)
The aim of this study was to evaluate the psychometric properties of the adapted Cyprus Greek Lexical List a-CYLEX (GR) in a sample of 194 Greek toddlers from the island of Crete with Standard Modern Greek (SMG) as their primary language. The a-CYLEX (GR) is a parental report checklist for assessing the receptive and expressive vocabulary skills of children aged 12 months to 3:6 years. Concurrent validity of the instrument was tested via correlations with the adapted Greek version of the Receptive One-Word Picture Vocabulary Test-II (ROWPVT-II), which was administered to 124 SMG-speaking children between the ages of 2 and 3:6 years. Test-retest reliability was tested by administering the instrument two times within a 2-week interval to 59 parents (30.41% of the total sample). Statistical analyses provided strong evidence for the high internal consistency and test-retest reliability of the a-CYLEX (GR). The role of the demographic variables in vocabulary performance and the frequency of each a-CYLEX (GR) word category by age were also investigated. In conclusion, the a-CYLEX (GR) is a parental report checklist that can be used by clinicians who are interested in assessing receptive and expressive vocabulary of children during toddlerhood.
Keywords: adapted Cyprus Greek Lexical List; demographic variables; expressive vocabulary; psychometric properties; receptive vocabulary